Endometriosis-associated clear cell carcinoma arising in caesarean section scar: a case report and review of the literature. Issue 1 (December 2016) - Ferrandina, Gabriella; Palluzzi, Eleonora; Fanfani, Francesco; Gentileschi, Stefano; Valentini, Anna; Mattoli, Maria; Pennacchia, Ilaria; Scambia, Giovanni; Zannoni, Gianfranco
Abstract Background Malignant transformation has been reported in approximately 1% of the endometriosis cases; herein, we report a case of clear cell endometrial carcinoma arising from endometriosis foci located within a caesarean section scar. Case presentation In November 2014, a Caucasian, 44-year-old woman was transferred to our institution because of severe respiratory failure due to massive lung embolism and rapid enlargement of a subcutaneous suprapubic mass. Abdomino-pelvic magnetic resonance showed a 10.5 × 5.0 × 5.0 cm subcutaneous solid mass involving the rectus abdominis muscle. Pelvic organs appeared normal, while right external iliac lymph nodes appeared enlarged (maximum diameter = 16 mm). A whole-body positron emission tomography/computed tomography scan showed irregular uptake of the radiotracer in the 22 cm mass of the abdominal wall, and in enlarged external iliac and inguinal lymph nodes. In December 2014, the patient underwent exploratory laparoscopy showing normal adnexae and pelvic organs; peritoneal as well as cervical, endometrial and vesical biopsies were negative. The patient was administered neo-adjuvant chemotherapy with carboplatin and paclitaxel, weekly, without benefit and then underwent wide resection of the abdominal mass, partial removal of rectus abdominis muscle and fascia, radical hysterectomy, bilateral salpingo-oophorectomy, and inguinal and pelvic lymphadenectomy. The muscular gap was repaired employing a gore-tex mesh while the external covering was made by a pedicled perforator fasciocutaneous anterolateral thigh flap. Final diagnosis was clear cell endometrial adenocarcinoma arising from endometriosis foci within the caesarean section scar. Pelvic and inguinal lymph nodes were metastatic. Tumor cells were positive for CK7 EMA, CKAE1/AE3, CD15, CA-125, while immunoreaction for Calretinin, WT1, estrogen, and progesterone receptors, cytokeratin 20, CD10, alpha fetoprotein, CDX2, TTF1, and thyroglobulin were all negative. Liver relapse occurred after 2 months; despite 3 cycles of pegylated liposomal doxorubicin (20 mg/m2, biweekly administration), the death of the patient disease occurred 1 month later. Conclusions Attention should be focused on careful evaluation of patient history in terms of pelvic surgery, and symptoms suggestive of endometriosis such as repeated occurrence of endometriosis nodules at CS scar, or cyclic pain, or volume changes of the nodules.